Bacteriostatic effect of CoO-TiO2 on Listeria monocytogenes by the presence of the co-catalytic CoO nanoparticles. Issue 5 (October 2020) - Sirsat, Sujata A.; Hecht, Oscar; Mirabal, Carlos; Pepe, David A.; Yang, Wenli; Mohammad, Zahra; Hadjiev, Viktor G.; Neal, Jack A.; Robles Hernandez, Francisco C.
Abstract: We present the antimicrobial properties of CoO-TiO2 tested against Listeria monocytogenes ( L. monocytogenes ), a harmful foodborne pathogenic microorganism. In this study we characterized the interaction of L. monocytogenes and CoO-TiO2 and identified the efficacy of CoO-TiO2 against L. monocytogenes using viability assays. The results show that CoO-TiO2 has a bacteriostatic effect on L. monocytogenes in both cases of presence and absence of indoor light conditions. While the pathogen viability is not affected, the pathogen cannot reproduce itself in the presence of CoO-TiO2 . Heat treatments promote back-diffusion of Co resulting in the precipitation of nanoparticles of CoO on the TiO2 substrate (grains) that enhances the catalytic benefits of the as synthesized CoO-TiO2 by 360 % in as synthesized conditions and 770 % in heat treated conditions. These results demonstrate that CoO-TiO2 could be used as an antimicrobial agent in the food processing industry (environment, direct application on foods, and on food contact surfaces).